2021
DOI: 10.1002/jemt.23933
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic characterization of petiole anatomy of Asteraceous taxa of Western Himalaya‐Pakistan

Abstract: Petiole anatomy of 15 species of family Asteraceae was examined which aimed to investigate petiolar anatomical structures for species level identification. Shandon Microtome was used for petiole histological preparations. Both qualitative and quantitative features were studied under microscope which showed significant variation in petiole, collenchyma, parenchyma shape/size, vascular bundles arrangement/size, and vessel elements quantity. Artemisia japonica Thunb., Cirsium vulgare (Savi) Ten., Myriactis nepale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…DPX mountant was placed on the slide for mounting, and the area received a cover slip. Each slide had a proper label and was dried [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…DPX mountant was placed on the slide for mounting, and the area received a cover slip. Each slide had a proper label and was dried [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Family Compositae recognized as Asteraceae is one of the leading families as well as the most economically important among the phanerogams families (Akhtar et al, 2021). Asteraceae is a cosmopolitan family comprised of around about 30,000 taxa with more the 1900 distinct genera (Gavrilović et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The palyno-morphometric study of Invasive, poisonous and allergenic genus Xanthium were carried by Coutinho et al, 2021. With the invention of microscopy, researchers observed that the high degree of variations found in pollen micromorphology, like psilate-echinate and lophate-echinolophate brings evolutionary relationships in Asteraceous species (Blackmore et al, 2010). Different clustering analyses will help in the differentiation of closely related Asteraceous taxa at genus-to-species levels based on pollen characters (Abid & Qaiser, 2023;Akhtar et al, 2021;Via do Pico et al, 2016). Hence, clustering analysis provided baseline information for the phylogeny of Asteraceae (Azizi et al, 2013).…”
mentioning
confidence: 99%
“…SEM has a high resolution, which reveals ultrastructure features that allow for micro‐morphological differences that are not achievable with light microscopy (LM) (Sadia et al, 2019; Luqman et al, 2019; Bahadur, Ahmad, Zafar, Gul, Ayaz, Ashfaq, Rubab, et al, 2019; Bahadur, Ahmad, Zafar, Sultana, Begum, Ashfaq, Gul, et al, 2019; Bahadur, Ahmad, Zafar, Sultana, Begum, Ashfaq, & Ullah, 2019; Ullah et al, 2019; Arshad et al, 2019; Khan, Abidin, et al, 2017; Khan, Ahmad, et al, 2017). The pollen surface has been greatly enhanced attributable to scanning electron microscopy (Akhtar et al, 2021; Aziz et al, 2022; Niazi et al, 2021; Rahman et al, 2019; Rozina Ahmad, Khan, et al, 2021; Rozina Ahmad, Zafar, et al, 2021). Scanning microscopy pollen research is also utilized to generate new terminology for defining pollen ornamentation, a statistical approach to pollen sculpturing, and even data analysis of the exine (Ijaz et al, 2022; Kanwal et al, 2022; Rashid, Ahmad, et al, 2019; Rashid, Zafar, et al, 2019; Hussain et al, 2021; Shah et al, 2021; Shahzad et al, 2021; Waheed et al, 2021; Yousaf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%